Interchromosomal recombination of the cellular oncogene c-myc with the immunoglobulin heavy chain locus in murine plasmacytomas is a reciprocal exchange. - Cory, S (1983)
The 15:12 chromosome translocations found in most murine plasmacytomas involve the cellular gene (c-myc) homologous to the oncogene (v-myc) of avian retrovirus MC29, Translocation links the c-myc gene of chromosome 15 to the immunoglobulin heavy (H) chain locus of chromosome 12, often within the switch recombination (S) region 5' to the alpha constant region (C alpha) gene. We have investigated c-myc rearrangements in 21 BALB/c plasmacytomas and three B lymphomas by Southern blot analysis. We show that the t(15;12) is a reciprocal chromosome exchange since most tumours contain not only a c-myc gene linked to the S alpha C alpha region but also a separate structure with S mu or S alpha linked to the c-myc 5'-flanking region. Analysis of the two rearrangement products cloned from plasmacytoma J558 suggests that one type of H locus target for translocation is an S alpha region recombined with S mu; two other targets appear to be other switched heavy chain genes and an unrearranged C alpha gene. Nearly all the chromosome 15 breakpoints fall within a 1.1-kb region spanning a 5' c-myc exon; hence scission of the transcriptional unit by translocation can account for the altered c-myc transcription in plasmacytomas. The c-myc breakpoint region lacks substantial homology with S mu or S alpha, arguing against homologous recombination as the translocation mechanism.